Accidental displacement of mandibular third molar root into the sublingual space and delayed removal. (13th September 2017) - Yamashita, Y.; Iwai, T.; Oaki, Y.; Omura, S.; Aoki, N.; Tohnai, I.
Abstract: Oral surgeons rarely experience accidental displacement of a mandibular impacted third molar into adjacent anatomical spaces as a complication. As any displaced third molar or its root is commonly removed at the time of displacement or within several weeks of the extraction, delayed removal several years after initial extraction is extremely rare. We report here accidental displacement of a mandibular third molar root into the sublingual space and a 5‐year delay in its removal. A 42‐year‐old woman presented to our department with pain and swelling in the lingual aspect of the left mandible. Computed tomography revealed a 15 × 11 × 9 mm lesion, with a similar density to that of the surrounding bone and involving the lingual cortex of the left mandible. A yellowish‐white hard tissue lesion was protruding from the lingual mucosa of the left mandibular ramus. The patient had undergone removal of a left impacted mandibular third molar at a private dental clinic 5 years earlier and we diagnosed the lesion as a remnant third molar root. The patient had not been informed by her dentist of accidental displacement of the tooth into the sublingual space after crown removal. After complete alleviation of inflammation, the patient underwent intraoral removal of the root under general anaesthesia. After elevating the lingual mucoperiosteal flap from the mandibular ramus to the premolar region, the root was easily removed using an elevator and forceps. Her postoperative course was uneventful and there were no complications such as lingual nerve injury.